Recovery and regeneration method of sodium ion battery positive electrode material

By immersing the cathode sheet of the used sodium ion battery into a metal salt solution and/or metal alkali solution for peeling, and mixing it with the sodium source and dopant to sinter, the lack of sodium ion battery recycling technology is solved, and the recycling and regeneration of the cathode material of the sodium ion battery is achieved with high efficiency and low cost, reducing environmental pollution and achieving sustainable utilization of resources.

CN119674297APending Publication Date: 2025-03-21湖州超钠新能源科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411783265.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The lack of sodium ion battery recycling technology suitable for industrialization in the prior art has made it difficult to effectively recycle and reuse waste materials of sodium ion battery, resulting in waste of resources and environmental pollution.

Method used

By immersing the cathode sheet of the used sodium ion battery into a metal salt solution and/or a metal alkali solution, peeling off the cathode material and the current collector to obtain a cathode powder, and mixing it with a sodium source and dopant for sintering treatment, the regeneration of the cathode material is achieved.

Benefits of technology

This method achieves efficient recycling and regeneration of the positive electrode material of sodium ion battery, reduces environmental pollution, realizes sustainable utilization of resources, and improves the comprehensive performance of recycled materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674297A_ABST
    Figure CN119674297A_ABST
Patent Text Reader

Abstract

The invention provides a recovery and regeneration method of a sodium ion battery positive electrode material. The method comprises the following steps: immersing a positive plate separated from the waste sodium-ion battery into a metal salt solution and / or a metal alkali solution to separate a positive electrode material from a current collector so as to obtain positive electrode powder; and drying and crushing the positive electrode powder, uniformly mixing with a sodium source and a doping agent, and sintering to obtain the regenerated positive electrode material. The recovery and regeneration method provided by the invention is simple in process, efficient and low in cost, and the sodium-ion battery positive electrode material obtained through recovery and regeneration has good comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new energy, and in particular relates to a method for recycling and regenerating positive electrode materials of sodium ion batteries. Background Art

[0002] With the outbreak of the new energy industry chain, lithium-ion batteries are facing huge demand. Lithium-ion batteries have quickly become the leader in the field of new energy due to their high capacity and long service life. However, due to the scarcity of lithium resources, the development of lithium-ion batteries may be subject to certain constraints. Therefore, it is urgent to develop a new battery system with low cost and abundant raw material resources. Sodium and lithium have similar physical and chemical properties, abundant reserves, low cost, and more sustainable development. Therefore, sodium-ion batteries are one of the most competitive alternatives to lithium-ion batteries. Sodium-ion battery layered oxide positive electrode materials have received increasing attention due to their high redox potential, high specific capacity, and low price, which has promoted the rapid development of the sodium-ion battery industry. The sharp increase in demand for lithium-ion batteries and sodium-ion batteries will inevitably lead to the generation of a large number of waste batteries. Waste lithium batteries and sodium batteries face the same environmental and economic challenges during the recycling process.

[0003] The life of lithium-ion batteries is generally 5-10 years. It is foreseeable that lithium-ion batteries will face large-scale scrapping in the near future, which will not only bring about a large waste of resources, but also cause serious pollution to the environment. At present, profits can usually be achieved by recycling high-value metals such as lithium and cobalt. However, due to the relatively low valuation of waste materials of sodium electricity, the recycling and regeneration technology for lithium batteries is not applicable to sodium electricity, and the existing technology has not proposed a sodium-ion battery recycling technology suitable for actual industrialization. Therefore, developing an efficient, low-cost, and scalable sodium-ion battery recycling and regeneration method is one of the problems that need to be solved urgently. Summary of the invention

[0004] In order to solve all or part of the above-mentioned technical problems, the present invention proposes a new technical route, which can realize the simple and efficient recycling and reuse of the positive electrode materials of sodium ion batteries, greatly reduce environmental pollution, and realize the sustainable utilization of resources.

[0005] The present invention provides the following technical solutions:

[0006] One of the purposes of the present invention is to provide a method for recycling anode materials of sodium ion batteries, comprising:

[0007] Immersing the positive electrode sheet separated from the waste sodium ion battery in a metal salt solution and / or a metal alkali solution to separate the positive electrode material from the current collector, thereby obtaining a positive electrode powder;

[0008] The positive electrode powder is dried and crushed, then uniformly mixed with a sodium source and a dopant and subjected to a first sintering treatment to obtain a regenerated positive electrode material.

[0009] The beneficial effect of the above technical solution is that the present invention uses a metal salt solution and / or a metal alkali solution to peel off the positive electrode sheet, which can achieve the purpose of removing the current collector. + It will undergo a strong proton exchange reaction with H+ in water, resulting in the generation of OH-, which will react with the binder (such as PVDF) to cause the binder to undergo a H / F cross-linking reaction, thereby causing the binder to fail, the bonding force between the positive electrode material and the current collector to disappear, and the positive electrode material can be easily peeled off from the current collector; at the same time, for the positive electrode material, a large amount of Na + The removal of Na will cause the collapse of the crystal structure of the material and the pulverization of the material. Therefore, the present invention adds certain metal ions to inhibit the Na + The Na + The outflow of sodium will lead to the formation of a sodium-deficient structure in the material, so the present invention uses a sodium source to supplement sodium; discarded batteries often experience complex operating conditions, and the structure of the positive electrode material may be significantly degraded, so the present invention uses a dopant to modify it, which is conducive to achieving structural stability of the regenerated positive electrode material. The present invention directly mixes and sintered the powder, sodium source, and dopant, which can avoid the cost increase caused by separate impurity removal (such as removing conductive agents, PVDF and other materials), and can also achieve the regeneration and performance improvement of the positive electrode material, with good economic and environmental benefits.

[0010] In some embodiments, the metal ions contained in the metal salt solution and / or the metal base solution include Na + , Li + , K + Mg 2+ 、Al 3+ , Ca 2+ 、Zn 2+ , Ca 2+ At least one of the metal ions, all of which have a certain effect of inhibiting the release of sodium ions. For example, the metal alkali solution includes one or more of NaOH, LiOH, KOH, Mg(OH)2, Al(OH)3, Cu(OH)2, Zn(OH)2, and Ca(OH)2, and the pH of the metal alkali solution is 7 to 13.

[0011] In some embodiments, the concentration of metal ions in the metal salt solution is 0.5 mol / L to 0.8×X mol / L, where X is the saturated concentration of metal ions in the metal salt solution.

[0012] In some embodiments, the concentration of metal ions in the metal alkali solution is 0.5 mol / L to 0.8×X mol / L, where X is the saturated concentration of metal ions in the metal alkali solution.

[0013] In some embodiments, the concentration of metal ions in the metal salt solution and / or the metal base solution is preferably 1 mol / L to 5 mol / L.

[0014] In some embodiments, the pH value of the metal salt solution and / or alkaline solution is preferably 8 to 10. A high pH value may easily lead to corrosion of the current collector, while a low pH value may result in poor separation of the powder and the electrode, resulting in low efficiency.

[0015] In some embodiments, immersing the positive electrode sheet in a metal salt solution and / or a metal alkali solution specifically includes: after the positive electrode sheet is immersed in the metal salt solution and the metal alkali solution, stirring is performed to accelerate the rate of peeling between the positive electrode and the current collector, and then filtering is performed to separate and recover the positive electrode and the current collector.

[0016] In some embodiments, the recycling method specifically includes: after obtaining the positive electrode powder, testing the element components and content information in the positive electrode powder, and determining the type and addition amount of the sodium source and dopant in the uniform mixture according to the element components and content information. For example, an ICP test is performed on the positive electrode powder.

[0017] In some embodiments, the temperature for drying the positive electrode powder is 100-200°C, preferably 100-160°C.

[0018] In some embodiments, the drying time is 2 to 15 hours, preferably 5 to 8 hours.

[0019] In some embodiments, the method of crushing the positive electrode powder includes one or a combination of mechanical crushing method and air flow crushing method.

[0020] Furthermore, after the crushing is completed, the positive electrode powder is sieved using a 200-400 mesh sieve.

[0021] Furthermore, the particle size D50 of the positive electrode powder obtained by the crushing is 4 to 16 um.

[0022] In some embodiments, the positive electrode powder has a molecular formula of Na x TMO2 (x ≥ 0.7), TM represents transition metal elements.

[0023] In some embodiments, the sodium source includes at least one of Na2CO3, NaHCO3, NaOH, C6H5Na3O7, Na2O, CH3COONa, and NaNO3.

[0024] In some embodiments, the added molar amount of the sodium source is 0.8 to 1.1 times, preferably 0.9 to 1.05 times, the difference between the sodium molar amounts of the regenerated positive electrode material and the positive electrode powder.

[0025] In some embodiments, the dopant includes a first dopant for providing a first doping element and a second dopant for providing a second doping element, the first dopant includes at least one of compounds containing Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Al, Mg, and Zn elements; the second dopant includes at least one of compounds containing Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Li, K, Ta, La, Nb, Zr, Mg, Zn, Al, Sn, Ru, Sr, W, Mo, B, F, and P elements, and the first doping element and the second doping element are different.

[0026] In some preferred embodiments, the first dopant includes at least one of compounds containing Cu, Zn, Ti, and Mg elements.

[0027] In some embodiments, the amount of the first dopant added is such that the molar ratio of the first doping element to the positive electrode powder is 0.001 to 0.6:1, preferably 0.005 to 0.1:1.

[0028] In some embodiments, the amount of the second dopant added is such that the molar ratio of the second doping element to the positive electrode powder is 0.001 to 0.2:1, preferably 0.005 to 0.1:1.

[0029] The doping treatment in the above technical solution is conducive to achieving the stability of the structure of the regenerated positive electrode material and improving the comprehensive performance of the material.

[0030] In some embodiments, the first sintering treatment includes a first stage of heat preservation sintering and a second stage of heat preservation sintering. The heat preservation temperature of the first stage of heat preservation sintering is 400℃~650℃, the heat preservation time is 2~10h, and the heating rate is 1~5℃ / min; the heat preservation temperature of the second stage of heat preservation sintering is 800℃~1200℃, the heat preservation time is 8~25h, and the heating rate is 1~5℃ / min. In addition to the positive electrode material, the general positive electrode sheet powder also has conductive agents (SP / KS-6 / CNT, etc.), PVDF, etc., and water washing can only effectively strip the current collector, and it is difficult to remove the conductive agent and PVDF. Therefore, the present invention adopts the first stage of heat preservation sintering to decompose and recover the conductive agent and residual binder in the positive electrode material, and the sintering treatment within the above temperature range can effectively remove them; after the conductive agent and PVDF are removed, in the second stage of heat preservation sintering, the sodium source and the dopant can effectively react with the positive electrode material, thereby realizing the regeneration of the material.

[0031] In some embodiments, the sintering atmosphere of the first sintering process includes an oxygen-containing gas, such as air or oxygen.

[0032] In some embodiments, the method further comprises: subjecting the mixed material containing the recycled positive electrode material and the coating agent to a second sintering treatment to obtain a finished positive electrode material. When the positive electrode powder is stripped of the current collector, the interface of the material will be damaged to a certain extent. The interface of the regenerated material is fragile, and the side reaction with the electrolyte is aggravated, resulting in deterioration of the material performance. Therefore, the present invention coats the surface of the regenerated material to effectively improve the comprehensive performance of the recycled material.

[0033] In some embodiments, the coating agent includes at least one of compounds containing Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Li, K, Ta, La, Nb, Zr, Mg, Zn, Al, Sn, Ru, Sr, W, Mo, B, F, P, and C elements.

[0034] In some embodiments, the molar ratio of the coating agent to the regenerated positive electrode material is 0.001 to 0.1:1, preferably 0.01 to 0.05:1.

[0035] In some embodiments, the holding temperature of the second sintering treatment is 250°C to 950°C, preferably 300°C to 500°C, the holding time is 2 to 15h, preferably 5 to 10h, and the heating rate is 1 to 5°C / min, preferably 2°C / min.

[0036] In some embodiments, the sintering atmosphere of the second sintering process is an oxygen-containing gas (such as air, oxygen) or nitrogen.

[0037] A second object of the present invention is to provide a regenerated positive electrode material or a finished positive electrode material obtained by the recycling and regeneration method described in any one of the above items.

[0038] In some embodiments, the molecular formula of the regenerated positive electrode material is Na a Ni b Fe c Mn d M e N f O g, wherein: 0<a≤1.1, 0≤b≤1, 0≤c≤1, 0≤d≤1, 0<e≤0.6, 0<f≤0.2, 0<g≤2(b+c+d+e+f=1), wherein the element M includes at least one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Al, Mg, and Zn, and the element N includes at least one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Li, K, Ta, La, Nb, Zr, Mg, Zn, Al, Sn, Ru, Sr, W, Mo, B, F, and P, and the elements M and N are different;

[0039] The element M, for example, comes from the first dopant, and the element N, for example, comes from the second dopant.

[0040] In some preferred embodiments, the element M includes at least one of Cu, Zn, Ti and Mg.

[0041] In some preferred embodiments, the molar ratio of the element M to the positive electrode powder is (0.005-0.1):1.

[0042] In some preferred embodiments, the molar ratio of the element N to the positive electrode powder is (0.005-0.1):1.

[0043] The third object of the present invention is to provide a sodium ion battery, which comprises a positive electrode, a negative electrode, an electrolyte and a separator, wherein the positive electrode comprises the regenerated positive electrode material and / or the finished positive electrode material described in the above technical solution.

[0044] Compared with the prior art, the present invention has at least the following beneficial effects:

[0045] (1) The present invention uses a metal salt solution and / or an alkaline solution to soak the positive electrode sheet, which can not only achieve simple and efficient stripping of the positive electrode material and the current collector on the positive electrode sheet, but also directly mix and sinter the recovered positive electrode powder with a sodium source and a dopant to repair and improve the comprehensive performance of the material. The sintering treatment used can simultaneously achieve the removal of the conductive agent and the binder in the material and the regeneration of the positive electrode material;

[0046] (2) Furthermore, when a metal salt solution and / or an alkaline solution is used to strip the positive electrode material, the metal ions therein can inhibit the Na + The material can be easily removed, which is beneficial to maintain the morphology and structural integrity of the material;

[0047] (3) The method for recycling and regenerating the positive electrode material of a sodium ion battery provided by the present invention is not only economical and environmentally friendly, but also easy to operate and conducive to industrialization, and the regenerated positive electrode material has good performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1a This is a SEM image of the positive electrode material recovered and regenerated in Example 1;

[0049] Figure 1b SEM of a newly prepared cathode material having the same chemical composition as the recycled material of Example 1;

[0050] Figure 2 This is the SEM image of the positive electrode material recovered and regenerated in Example 2;

[0051] Figure 3 This is a SEM image of the positive electrode material recovered and regenerated in Example 3;

[0052] Figure 4 This is a SEM image of the positive electrode material recovered and regenerated in Example 4;

[0053] Figure 5a This is a SEM image of the positive electrode material recovered and regenerated in Example 5;

[0054] Figure 5b is a SEM image of a newly prepared positive electrode material having the same chemical composition as the recycled material of Example 5;

[0055] Figure 6 This is the SEM image of the positive electrode material recovered and regenerated in Comparative Example 1. DETAILED DESCRIPTION

[0056] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention. The specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.

[0057] Example 1

[0058] The cylindrical 32140 sodium ion battery is disassembled to obtain the positive electrode sheet. The positive electrode active material in the positive electrode sheet is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.

[0059] Dissolve Na2SO4 in water to obtain a stripping solution. + The concentration is 1 mol / L;

[0060] The positive electrode sheet was directly immersed in the above stripping solution, and after sufficient stirring for reaction, the positive electrode powder and the current collector were quickly stripped, and the stripped positive electrode material was dried at 120° C. for 12 h, and then mechanically crushed and sieved through a 200-mesh sieve to obtain a powder with a particle size of D50=11.5 μm;

[0061] The crushed and sieved powder is evenly mixed with Na2CO3, Cu2(OH)2CO3 and ZrO2 to obtain a first mixed material, wherein the added molar amount of the sodium source is 1.03 times the difference between the sodium molar amount of the regenerated positive electrode material to be obtained and the positive electrode powder; the copper source is added in an amount such that the molar ratio of the Cu element to the positive electrode powder is 0.03:1, and the zirconium source is added in an amount such that the molar ratio of the Zr element to the positive electrode powder is 0.01:1;

[0062] The first mixed material is subjected to a first sintering treatment, in an air atmosphere, firstly heated to 500° C. at a heating rate of 2° C. / min and kept at that temperature for 5 h, then heated to 900° C. at a heating rate of 2° C. / min and kept at that temperature for 15 h;

[0063] The powder obtained after the first sintering treatment is mixed with H3BO3 to obtain a second mixed material, and the second mixed material is subjected to a second sintering treatment; wherein the amount of coating agent added is such that the molar ratio of the added molar amount of coating element B to the regenerated positive electrode material is 0.01:1; the second sintering treatment is carried out in an oxygen atmosphere, the temperature is increased to 400°C at a heating rate of 2°C / min and maintained for 8 hours.

[0064] Figure 1a This is the SEM image of the positive electrode material recovered and regenerated in Example 1. Figure 1b This is a SEM of a freshly prepared positive electrode material with the same chemical composition as the recycled material in Example 1.

[0065] Example 2

[0066] The cylindrical 32140 sodium ion battery is disassembled to obtain the positive electrode sheet. The positive electrode active material in the positive electrode sheet is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.

[0067] KCl is dissolved in water to obtain a stripping solution. + The concentration is 3 mol / L;

[0068] The positive electrode sheet was directly immersed in the above stripping solution, and after sufficient stirring for reaction, the positive electrode powder and the current collector were quickly stripped, and the stripped positive electrode material was dried at 120° C. for 12 h, and then mechanically crushed and sieved through a 200-mesh sieve to obtain a powder with a particle size of D50=10.3 μm;

[0069] The crushed and sieved powder is evenly mixed with Na2CO3, TiO2 and MgO to obtain a first mixed material, wherein the added molar amount of the sodium source is 1.03 times the difference between the sodium molar amount of the regenerated positive electrode material to be obtained and the positive electrode powder; the added amount of the titanium source is such that the molar ratio of the Ti element to the positive electrode powder is 0.05:1, and the added amount of the magnesium source is such that the molar ratio of the Mg element to the positive electrode powder is 0.05:1;

[0070] The first mixed material is subjected to a first sintering treatment, in an air atmosphere, firstly heated to 500° C. at a heating rate of 2° C. / min and kept at that temperature for 5 h, then heated to 900° C. at a heating rate of 2° C. / min and kept at that temperature for 15 h;

[0071] The powder obtained after the first sintering treatment is mixed with the coating agent Al2O3 to obtain a second mixed material, and the second mixed material is subjected to a second sintering treatment; wherein the amount of the coating agent added is such that the molar ratio of the added molar amount of the coating element Al to the regenerated positive electrode material is 0.02:1; the second sintering treatment is carried out in an oxygen atmosphere, the temperature is increased to 600°C at a heating rate of 2°C / min and maintained for 8 hours.

[0072] Figure 2 This is the SEM image of the positive electrode material recovered and regenerated in Example 2.

[0073] Example 3

[0074] The square 50Ah sodium ion battery was disassembled to obtain the positive electrode sheet. The positive electrode active material in the positive electrode sheet is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2;

[0075] Dissolve Na2CO3 in water to obtain a stripping solution. + The concentration is 0.5 mol / L;

[0076] The positive electrode sheet is directly immersed in the above stripping solution, and after sufficient stirring for reaction, the positive electrode powder and the current collector are quickly stripped, and the stripped positive electrode material is dried at 120° C. for 12 h, and then subjected to air flow crushing and sieving with a 200-mesh sieve to obtain a powder with a particle size of D50=6.2 μm;

[0077] The crushed and sieved powder is evenly mixed with Na2CO3, TiO2 and CuO to obtain a first mixed material, wherein the molar amount of sodium carbonate added is 0.95 times the difference between the molar amount of sodium in the regenerated positive electrode material to be obtained and the positive electrode powder; the amount of titanium source added is such that the molar ratio of Ti element to the positive electrode powder is 0.04:1, and the amount of copper source added is such that the molar ratio of Cu element to the positive electrode powder is 0.03:1;

[0078] The first mixed material is subjected to a first sintering treatment, in an air atmosphere, firstly heated to 500° C. at a heating rate of 2° C. / min and kept at that temperature for 5 h, then heated to 980° C. at a heating rate of 2° C. / min and kept at that temperature for 15 h;

[0079] The powder obtained after the first sintering treatment is mixed with the coating agent Al2O3 to obtain a second mixed material, and the second mixed material is subjected to a second sintering treatment; wherein the amount of the coating agent added is such that the molar ratio of the added molar amount of the coating element Al to the regenerated positive electrode material is 0.02:1; the second sintering treatment is carried out in an air atmosphere, the temperature is increased to 600°C at a heating rate of 2°C / min and maintained for 5 hours.

[0080] Figure 3 This is the SEM image of the positive electrode material recovered and regenerated in Example 3.

[0081] Example 4

[0082] The square 50Ah sodium ion battery was disassembled to obtain the positive electrode sheet. The positive electrode active material in the positive electrode sheet is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2;

[0083] LiOH is dissolved in water to obtain a stripping solution. + The concentration is 1 mol / L;

[0084] The positive electrode sheet is directly immersed in the above stripping solution, and after sufficient stirring for reaction, the positive electrode powder and the current collector are quickly stripped, and the stripped positive electrode material is dried at 120° C. for 12 h, and then mechanically crushed and sieved through a 200-mesh sieve to obtain a powder with a particle size of D50=4.5 μm;

[0085] The crushed and sieved powder is evenly mixed with Na2CO3, La2O3 and ZnO to obtain a first mixed material, wherein the added molar amount of the sodium source is 1.03 times the difference between the sodium molar amount of the regenerated positive electrode material to be obtained and the positive electrode powder; the added amount of the lanthanum source is such that the molar ratio of the La element to the positive electrode powder is 0.02:1, and the added amount of the zinc source is such that the molar ratio of the Zn element to the positive electrode powder is 0.02:1;

[0086] The first mixed material is subjected to a first sintering treatment, in an air atmosphere, firstly heated to 500° C. at a heating rate of 2° C. / min and kept at that temperature for 5 h, then heated to 1000° C. at a heating rate of 2° C. / min and kept at that temperature for 15 h;

[0087] The powder obtained after the first sintering treatment is mixed with the coating agent H3BO3 to obtain a second mixed material, and the second mixed material is subjected to a second sintering treatment; wherein the amount of the coating agent added is such that the molar ratio of the added molar amount of the coating element B to the regenerated positive electrode material is 0.02:1; the second sintering treatment is carried out in an air atmosphere, the temperature is increased to 400°C at a heating rate of 2°C / min and kept warm for 8 hours.

[0088] Figure 4 This is the SEM image of the positive electrode material recovered and regenerated in Example 4.

[0089] Example 5

[0090] The cylindrical 32140 sodium ion battery is disassembled to obtain the positive electrode sheet. The positive electrode active material in the positive electrode sheet is Na 0.90 Ni 0.25 Fe 0.40 Mn 0.35 O2;

[0091] Dissolve Ca(NO3)2 in water to obtain a stripping solution. 2+ The concentration is 1.5 mol / L;

[0092] The positive electrode sheet was directly immersed in the above stripping solution, and after sufficient stirring for reaction, the positive electrode powder and the current collector were quickly stripped, and the stripped positive electrode material was dried at 120° C. for 12 h, and then mechanically crushed and sieved through a 200-mesh sieve to obtain a powder with a particle size of D50=6.3 μm;

[0093] The crushed and sieved powder is evenly mixed with Na2CO3, MgO and K2CO3 to obtain a first mixed material, wherein the added molar amount of the sodium source is 1.03 times the difference between the sodium molar amount of the regenerated positive electrode material to be obtained and the positive electrode powder; the added amount of the magnesium source is such that the molar ratio of the Mg element to the positive electrode powder is 0.03:1, and the added amount of the potassium source is such that the molar ratio of the K element to the positive electrode powder is 0.01:1;

[0094] The first mixed material is subjected to a first sintering treatment, in an air atmosphere, firstly heated to 500° C. at a heating rate of 2° C. / min and kept at that temperature for 5 h, then heated to 930° C. at a heating rate of 2° C. / min and kept at that temperature for 15 h;

[0095] The powder obtained after the first sintering treatment is mixed with the coating agent TiO2 to obtain a second mixed material, and the second mixed material is subjected to a second sintering treatment, wherein the amount of the coating agent added is such that the molar ratio of the added molar amount of the coating element Ti to the regenerated positive electrode material is 0.03:1; the second sintering treatment is carried out in an air atmosphere, and the temperature is increased to 650°C at a heating rate of 2°C / min and maintained for 5 hours.

[0096] Figure 5a This is the SEM image of the positive electrode material recovered and regenerated in Example 5. Figure 5b This is an SEM image of a newly prepared positive electrode material having the same chemical composition as the recycled material in Example 5.

[0097] Comparative Example 1

[0098] This comparative example is basically the same as Example 1, except that the stripping liquid in Example 1 is replaced by pure water.

[0099] Figure 6 This is the SEM image of the positive electrode material recovered and regenerated in Comparative Example 1.

[0100] Comparative Example 2

[0101] This comparative example is basically the same as Example 1, except that there is no second sintering treatment.

[0102] Comparative Example 3

[0103] This comparative example is basically the same as Example 1, except that during the first sintering treatment, the positive electrode powder is only mixed with the sodium source, and no Cu or Zr doping elements are introduced.

[0104] from Figure 1a and 1b , Figure 5a and 5b Comparison of sample morphology shows that the microscopic morphology of the recycled positive electrode material is not much different from that of the corresponding new positive electrode material.

[0105] The positive electrode active materials prepared in each example and comparative example were made into button-type half-cells to test their electrochemical performance, and the new non-regenerated positive electrode active materials corresponding to each example were used as blank controls.

[0106] The specific test method is as follows: the sodium ion battery positive electrode material prepared by recycling each embodiment and comparative example is used as the positive electrode, the metal sodium sheet is used as the negative electrode, the glass fiber membrane is used as the separator, and the NaPF6 / propylene carbonate mixed solution is used as the electrolyte to assemble a sodium ion battery, and the charge and discharge test is performed, the current density is 15mA / g, the voltage range is 2.5-4.1V, and the test temperature is 25°C. The test results are recorded in Table 1.

[0107] Table 1 Performance of the positive electrode materials recovered from each embodiment and comparative example

[0108]

[0109]

[0110] It can be seen from the above table that the positive electrode active materials regenerated and recovered in various embodiments of the present invention have little difference in electrochemical performance compared with the newly prepared positive electrode active materials with the same chemical composition, and meet the requirements for recycling.

[0111] The stripping liquid used in Comparative Example 1 is a pure aqueous solution (without metal ions). During the positive electrode sheet stripping process, the positive electrode material is severely de-Naed, resulting in structural fragmentation. Therefore, broken particles exist in the morphology of the recovered positive electrode material. Moreover, the first-cycle gram capacity, cycle and rate performance of the battery made of the recovered positive electrode active material are poor.

[0112] By comparing Example 1 with Comparative Examples 2 and 3, it is found that both doping and coating can significantly improve the electrochemical performance of the material.

[0113] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0114] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0115] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.

Claims

1. A method for recycling positive electrode materials of sodium ion batteries, characterized in that: include: Immersing the positive electrode sheet separated from the waste sodium ion battery in a metal salt solution and / or a metal alkali solution to separate the positive electrode material from the current collector, thereby obtaining a positive electrode powder; The positive electrode powder is dried and crushed, then uniformly mixed with a sodium source and a dopant and subjected to a first sintering treatment to obtain a regenerated positive electrode material.

2. The method for recycling the positive electrode material of a sodium ion battery according to claim 1, characterized in that: The metal ions contained in the metal salt solution and the metal alkali solution include Na + , Li + , K + Mg 2+ 、Al 3+ , Cu 2+ 、Zn 2+ , Ca 2+ At least one of; and / or, the concentration of metal ions in the metal salt solution is 0.5 mol / L to 0.8×X mol / L, where X is the saturated concentration of metal ions in the metal salt solution; and / or, the concentration of metal ions in the metal alkali solution is 0.5 mol / L to 0.8×X mol / L, where x is the saturation concentration of metal ions in the metal alkali solution; And / or, the sodium source includes at least one of Na2CO3, NaHCO3, NaOH, C6H5Na3O7, Na2O, CH3COONa, and NaNO3; And / or, the added molar amount of the sodium source is 0.8 to 1.1 times the difference between the sodium molar amount of the regenerated positive electrode material and the sodium molar amount of the positive electrode powder; And / or, the first sintering treatment includes a first stage of heat preservation sintering and a second stage of heat preservation sintering, the heat preservation temperature of the first stage of heat preservation sintering is 400°C to 650°C, the heat preservation time is 2 to 10 hours, and the heating rate is 1 to 5°C / min; the heat preservation temperature of the second stage of heat preservation sintering is 800°C to 1200°C, the heat preservation time is 8 to 25 hours, and the heating rate is 1 to 5°C / min; And / or, the sintering atmosphere of the first sintering process includes an oxygen-containing gas.

3. The method for recycling the positive electrode material of a sodium ion battery according to claim 2, characterized in that: The dopant includes a first dopant for providing a first doping element and a second dopant for providing a second doping element, the first dopant includes at least one of a compound containing Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Al, Mg, and Zn, the second dopant includes at least one of a compound containing Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Li, K, Ta, La, Nb, Zr, Mg, Zn, Al, Sn, Ru, Sr, W, Mo, B, F, and P, and the first doping element and the second doping element are different; Preferably, the amount of the first dopant added is such that the molar ratio of the first doping element to the positive electrode powder is (0.001-0.6):1, and the amount of the second dopant added is such that the molar ratio of the second doping element to the positive electrode powder is (0.001-0.2):1; Preferably, the first dopant includes at least one of compounds containing Cu, Zn, Ti, and Mg elements.

4. The method for recycling and regenerating the positive electrode material of a sodium ion battery according to claim 1, characterized in that: The method further comprises: at least uniformly mixing the regenerated positive electrode material with a coating agent and performing a second sintering treatment to obtain a finished positive electrode material.

5. The method for recycling the positive electrode material of a sodium ion battery according to claim 4, characterized in that: The coating agent includes at least one of compounds containing Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Li, K, Ta, La, Nb, Zr, Mg, Zn, Al, Sn, Ru, Sr, W, Mo, B, F, P, and C elements; And / or, the molar ratio of the coating agent to the regenerated positive electrode material is (0.001N0.1):1; And / or, the holding temperature of the second sintering treatment is 250°C to 950°C, the holding time is 2 to 15 h, and the heating rate is 1 to 5°C / min: And / or, the sintering atmosphere of the second sintering treatment is an oxygen-containing gas or nitrogen.

6. The method for recycling and regenerating the positive electrode material of a sodium ion battery according to claim 1, characterized in that: Specifically, it includes: After obtaining the positive electrode powder, test the element components and content information in the positive electrode powder, and determine the types and addition amounts of the sodium source and the dopant according to the element components and content information.

7. The method for recycling and regenerating the positive electrode material of a sodium ion battery according to claim 1, characterized in that: The temperature of the drying is 100 to 200°C, and / or the time of the drying is 2 to 15 h.

8. The method for recycling and regenerating the positive electrode material of a sodium ion battery according to claim 1, characterized in that: The method of the crushing includes one or a combination of more of a mechanical crushing method and a gas flow crushing method; Preferably, after the crushing is completed, the positive electrode powder is sieved with a 200-400 mesh sieve; Preferably, the particle size D50 of the positive electrode powder obtained by the crushing is 4 to 16 μm.

9. The regenerated positive electrode material or the finished positive electrode material obtained by the recycling and regeneration method according to any one of claims 1 to 8; Preferably, the molecular formula of the regenerated positive electrode material is NaaNibFe.MndM.NfOg, wherein: 0 < a ≤ 1.1, 0 ≤ b ≤ 1, 0 ≤ c ≤ 1, 0 ≤ d ≤ 1, 0 < e ≤ 0.6, 0 < f ≤ 0.2, 0 < g ≤ 2 (b + c + d + e + f = 1), wherein the element M includes at least one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Al, Mg, Zn, and the element N includes at least one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Li, K, Ta, La, Nb, Zr, Mg, Zn, Al, Sn, Ru, Sr, W, Mo, B, F, P, and the elements M and N are different; More preferably, the element M includes at least one of Cu, Zn, Ti, Mg.

10. A sodium ion battery comprising a positive electrode, a negative electrode, an electrolyte and a separator, characterized in that: The positive electrode includes the regenerated positive electrode material and / or the finished positive electrode material described in 9.